Investigation of the Phenomenological and Psychopathological Features of Trichotillomania in an Italian Sample - Bottesi, Gioia; Cerea, Silvia; Razzetti, Enrico; Sica, Claudio; Frost, Randy O.; Ghisi, Marta (Frontiers in Psychology, 2016)
Trichotillomania (TTM) is still a scarcely known and often inadequately treated disorder in Italian clinical settings, despite growing evidence about its severe and disabling consequences. The current study investigated the phenomenology of TTM in Italian individuals; in addition, we sought to examine patterns of self-esteem, anxiety, depression, and OCD-related symptoms in individuals with TTM compared to healthy participants. The current study represents the first attempt to investigate the phenomenological and psychopathological features of TTM in Italian hair pullers. One hundred and twenty-two individuals with TTM were enrolled: 24 were assessed face-to-face (face-to-face group) and 98 were recruited online (online group). An additional group of 22 face-to-face assessed healthy controls (HC group) was included in the study. The overall female to male ratio was 14:1, which is slightly higher favoring female than findings reported in literature. Main results revealed that a higher percentage of individuals in the online group reported pulling from the pubic region than did face-to-face participants; furthermore, the former engaged in examining the bulb and running the hair across the lips and reported pulling while lying in bed at higher frequencies than the latter. Interestingly, the online TTM group showed greater functional and psychological impairment, as well as more severe psychopathological characteristics (self-esteem, physiological and social anxiety, perfectionism, overestimation of threat, and control of thoughts), than the face-to-face one. Differences between the two TTM groups may be explained by the anonymity nature of the online group, which may have led to successful recruitment of more serious TTM cases, or fostered more open answers to questions. Overall, results revealed that many of the phenomenological features of Italian TTM participants matched those found in U.S. clinical settings, even though some notable differences were observed; therefore, cross-cultural invariance might represent a characteristic of OCD-related disorders.